Optimalisasi Keuntungan Penjualan Beras di Toko Berkah - Panjaitan, Hadid Akhyarsyah; Harahap, Muhammad Irham; Christoval, Peter; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
This research aims to optimize the profit of rice sales at Toko Berkah using the Simplex Method with the QM for Windows application. Toko Berkah, as a rice store, faces challenges in planning and managing rice product inventory to achieve maximum profit. This study applies the Simplex Method, a mathematical programming technique, to identify the optimal combination of rice inventory that can enhance sales profit. The research steps include historical sales data analysis, identification of decision variables, and formulation of a mathematical model based on optimal objectives. The QM for Windows application is used as a tool to execute the Simplex Method and analyze its results. The study also evaluates the impact of optimization on profit, inventory efficiency, and customer satisfaction. The findings of this research are expected to provide practical guidance to rice store owners or similar business entities in managing inventory and planning sales. Furthermore, this study may contribute to the development of optimization methods applicable to small and medium-sized businesses, particularly in the rice sector.